Exercise intervention improves quality of life in older adults after myocardial infarction: randomised clinical trial. Issue 21 (6th March 2020) - Campo, Gianluca; Tonet, Elisabetta; Chiaranda, Giorgio; Sella, Gianluigi; Maietti, Elisa; Bugani, Giulia; Vitali, Francesco; Serenelli, Matteo; Mazzoni, Gianni; Ruggiero, Rossella; Villani, Giovanni; Biscaglia, Simone; et al.
Abstract : Objective: To establish the benefits of an early, tailored and low-cost exercise intervention in older patients hospitalised for acute coronary syndrome (ACS). Methods: The study was a multicentre, randomised assessment of an exercise intervention in patients with ACS ≥70 years with reduced physical performance (as defined by the short physical performance battery (SPPB), value 4–9). The exercise intervention included four supervised sessions (1, 2, 3, 4 months after discharge) and home-based exercises. The control group attended a health education programme only. The outcomes were the 6-month and 1-year effects on physical performance, daily activities, anxiety/depression and quality of life. Finally, 1-year occurrence of adverse events was recorded. Results: Overall, 235 patients with ACS (median age 76 (73–81) years) were randomised 1 month after ACS. Exercise and control groups were well balanced. Exercise intervention improved 6-month and 1-year grip strength and gait speed. Exercise intervention was associated with a better quality of life (as measured by EuroQol-visual analogue scale at 6 months 80 (70–90) vs 70 (50–80) points, p<0.001 and at 1 year 75 (70–87) vs 65 (50–80) points, p<0.001) and with a reduced perception of anxiety and/or depression (6 months: 21% vs 42%, p=0.001; 1 year 32% vs 47%, p=0.03). The occurrence of cardiac death and hospitalisation for cardiac cause was lower in the intervention group (7.5% vs 17%, p=0.04). Conclusions: The proposed early, tailored, low-cost exercise intervention improves mobility, daily activities, quality of life and outcomes in older patients with ACS. Larger studies are needed to confirm the clinical benefit. Trial registration number: NCT03021044 .